Protective effects of tiopronin on oxidatively challenged human lung carcinoma cells (A549). (3rd May 2020) - Beltz, Justin; Chernatynskaya, Anna; Pfaff, Annalise; Ercal, Nuran
Abstract: Tiopronin (MPG) is a thiol antioxidant drug that has been explored as a treatment for various oxidative stress-related disorders. However, many of its antioxidant capabilities remain untested in well-validated cell models. To more thoroughly understand the action of this promising pharmaceutical compound against acute oxidative challenge, A549 human lung carcinoma cells were exposed to tert -butyl hydroperoxide ( t BHP) and treated with MPG. Analyses of cell viability, intracellular glutathione (GSH) levels, and the prevalence of reactive oxygen species (ROS) and mitochondrial superoxide were used to examine the effects of MPG on t BHP-challenged cells. MPG treatment suppressed intracellular ROS and mitochondrial superoxide and prevented t BHP-induced GSH depletion and apoptosis. These results indicate that MPG is effective at preserving redox homeostasis against acute oxidative insult in A549 cells if present at sufficient concentrations during exposure to oxidants such as t BHP. The effects of treatment gleaned from this study can inform experimental design for future in vivo work on the therapeutic potential of MPG.